Safe-margin surgery by plastic reconstruction in extremities or parietal trunk soft tissue sarcoma: A tertiary single centre experience. Issue 3 (March 2022) - Samà, Laura; Binder, Jean Philippe; Darrigues, Lauren; Couturaud, Benoit; Boura, Benoit; Helfre, Sylvie; Chiche, Laurent; Nicolas, Nayla; Tzanis, Dimitri; Bouhadiba, Toufik; Gentile, Damiano; Perlbarg-Samson, Julie; et al.
Abstract: Introduction: Tertiary centers recruit a large proportion of locally advanced or recurrent soft tissue sarcomas (STSs) that may have been preoperatively irradiated. The objective of this study was to evaluate the results of oncoplastic surgery (OPS) for patients affected by extremities or parietal trunk STS. Materials and methods: This retrospective study includes patients who underwent a flap reconstruction after sarcoma resection between January 2018 and December 2020 at Institut Curie. The primary endpoint was the evaluation of the impact of OPS on the quality of surgical margins. The secondary endpoint was to quantify the morbidity of OPS and identify predictive factors for wound complications. Results: Of 211 patients, 89 (42.2%) had a flap reconstruction. Surgery was realized on an irradiated field in 56 (62.9%) patients. Without OPS, all patients were candidates either for amputation (n = 9, 10.1%) due to vessels/nerve infiltration, or R1/R2 resection (n = 80, 89.9%). Seventy-two (80.0%) pedicle flaps and 18 (20.0%) free flaps were used. No R2 resections were performed. R0 and R1 margins were achieved in 82 (92.1%) and 7 (7.9%), respectively. The median closest margin was 3 mm (IQR 1–6 mm). Among R1 patients, 5 had positive margins along a preserved critical structure, 2 patients had well-differentiated liposarcomas. The surgical morbidity rate was 33.3% (30/90 flaps). The reoperation rate was 15.7% (14/89 patients). Conclusions: In a referral sarcoma center, the collaboration between the surgical oncologist and the plastic surgery team should be considered upfront in the surgical plan, allowing the most adequate wide oncological resection with acceptable postoperative morbidity.